A Comprehensive Molecular and Epidemiological Characterization of Influenza Viruses Circulating 2016–2020 in North Macedonia - Kuzmanovska, Maja; Boshevska, Golubinka; Janchevska, Elizabeta; Buzharova, Teodora; Simova, Milica; Peshnacka, Aneta; Nikolovska, Gordana; Kochinski, Dragan; Ilioska, Radica Stoleska; Stavridis, Kristina; Mikikj, Vladimir; Kuzmanovska, Gordana; et al. (Frontiers in Microbiology, 2021)
Influenza viruses know no boundaries, representing an example of rapid virus evolution combined with pressure exerted by the host’s immune system. Seasonal influenza causes 4–50 million symptomatic cases in the EU/EEA each year, with a global death toll reaching 650,000 deaths. That being the case, in 2014 North Macedonia introduced the sentinel surveillance in addition to the existing influenza surveillance in order to obtain more precise data on the burden of disease, circulating viruses and to implement timely preventive measures. The aims of this study were to give a comprehensive virological and epidemiological overview of four influenza seasons (2016–2020), assess the frequency and distribution of influenza circulating in North Macedonia and to carry out molecular and phylogenetic analyses of the hemagglutinin (HA) and neuraminidase (NA) genes of influenza A(H1N1)pdm09, A(H3N2) from ILI and SARI patients. Our results showed that out of 1,632 tested samples, 46.4% were influenza positive, with influenza A(H1N1)pdm09 accounting for the majority of cases (44%), followed by influenza B (32%) and A(H3N2) (17%). By comparing the sentinel surveillance system to the routine surveillance system, we showed that the newly applied system works efficiently and gives great results in the selection of cases. Statistically significant differences (p = < 0.0000001) were observed when comparing the number of reported ILI cases among patients aged 0–4, 5–14, 15–29, and 30–64 years to the reference age group. The phylogenetic analysis of the HA sequences unveiled the resemblance of mutations circulating seasonally worldwide, with a vast majority of circulating viruses belonging to subclade 6B.1A. The PROVEAN analysis showed that the D187A substitution in the receptor binding site (RBS) of the A(H1N1)pdm09 HA has a deleterious effect on the its function. The A(H3N2) viruses fell into the 3C.2a and 3C.3a throughout the analyzed seasons. Molecular characterization revealed that various substitutions in the A(H3N2) viruses gradually replaced the parental variant in subsequent seasons before becoming the dominant variant. With the introduction of sentinel surveillance, accompanied by the advances made in whole-genome sequencing and vaccine therapeutics, public health officials can now modify their approach in disease management and intervene effectively and in a timely manner to prevent major morbidity and mortality from influenza.